2020
DOI: 10.1002/hep4.1556
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Proteome of Circulating Extracellular Vesicles as Potential Biomarkers for NASH

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently one of most common forms of chronic liver disease globally. NAFLD represents a wide spectrum of liver involvement from nonprogressive isolated steatosis to nonalcoholic steatohepatitis (NASH), characterized by liver necroinflammation and fibrosis and currently one of the top causes of end‐stage liver disease and hepatocellular carcinoma. At present, there is a lack of effective treatments, and a central barrier to the development of therapies is the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 42 publications
1
66
0
Order By: Relevance
“…Markers were selected based on the Minimal Information for Studies of Extracellular Vesicles (MISEV) guidelines for confirming the presence of EV-enriched proteins and include those derived from the plasma membrane, endosomal pathway, and cytosol [21]. The panel was comprised of tetraspanins CD9, CD63 and CD81, and the cytosolic protein tumour susceptibility gene 101 (TSG101), as well as the hepatocyte-specific surface protein asialoglycoprotein receptor 1 (ASGR1), which is known to be expressed on EVs derived from this cell type [4,22]. The expression of protein markers was quantified by LCMS and assessed for variability between subjects in AM and PM EVs ( Figure 3D-H).…”
Section: Normal Variabilitymentioning
confidence: 99%
“…Markers were selected based on the Minimal Information for Studies of Extracellular Vesicles (MISEV) guidelines for confirming the presence of EV-enriched proteins and include those derived from the plasma membrane, endosomal pathway, and cytosol [21]. The panel was comprised of tetraspanins CD9, CD63 and CD81, and the cytosolic protein tumour susceptibility gene 101 (TSG101), as well as the hepatocyte-specific surface protein asialoglycoprotein receptor 1 (ASGR1), which is known to be expressed on EVs derived from this cell type [4,22]. The expression of protein markers was quantified by LCMS and assessed for variability between subjects in AM and PM EVs ( Figure 3D-H).…”
Section: Normal Variabilitymentioning
confidence: 99%
“…Besides such changing cargo, also changes in the absolute numbers of circulating EVs may be observed during disease. For example, an elevated number of circulating EVs is observed in NASH patients, with the EV-numbers strongly correlating to NASH clinical characteristics and disease severity ( 139 ). These findings reflect the elevated number of circulating EVs identified in mice with diet-induced NASH ( 140 ).…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…The diagnostic accuracy presented AUROCs between 0.93 and 1. Moreover, Povero et al [24] recently described the application of SOMAScan® to the proteomic characterization of circulating extracellular vesicles (EVs). The data demonstrated that the quantity and protein constituents of circulating EVs provided strong evidence for the utility of EV proteinbased liquid biopsies for NAFLD/NASH diagnosis.…”
Section: Novel Technologies For Biomarkers Discovery Applied To Nafldmentioning
confidence: 99%